Analisis Hubungan Gaji, Tunjangan, dan Produktivitas Karyawan terhadap Profitabilitas Perusahaan - Cindi Ida Febrianti; Lathifatul Fikriyah; Rafika Meila Sari (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2026)
This study aims to analyze the relationship between salaries, allowances, and employee productivity on company profitability. Human resources are an important factor in determining organizational success because employee quality and performance directly influence the achievement of company goals. Providing appropriate compensation, including salaries and allowances, can increase employee motivation, job satisfaction, and loyalty, thereby encouraging higher work productivity. High productivity reflects the company’s ability to utilize resources effectively and efficiently in order to produce optimal output. In addition, employee turnover is an important aspect that must be considered because it may affect operational stability and the company’s effectiveness in achieving business targets. Profitability is used as the main indicator to assess the company’s ability to generate profits from its operational activities. This study applies a quantitative method with an approach that examines the relationships among variables to obtain an overview of the influence of compensation and productivity on company profitability. The results of this study are expected to provide insights and recommendations for companies in managing human resources more effectively in order to improve financial performance sustainably.